Reducing racism in Aboriginal health care in Australia: Where does cultural education fit? - Durey, Angela (Blackwell Publishing Asia, 2010)
Objective: This paper discusses whether educating health professionals and undergraduate students in culturally respectful health service delivery is effective in reducing racism, improving practice and lessening the disparities in health care between Aboriginal and non-Aboriginal Australians. Approach: The paper supports the concept of race as a social construction that is discursively produced and reproduced. Studies on the effectiveness of cross-cultural education for undergraduate students and health professionals to reduce racism and deliver culturally respectful health care to indigenous or minority populations are examined for evidence of sustained improvements to practice. Conclusion: Programs in culturally respectful health care delivery can lead to short-term improvements to practice. Sustained change is more elusive as few programs conducted long-term evaluations. Long-term evaluation of programs in culturally respectful health care delivery is necessary to identify whether early changes to behavior and practices are sustained. Strategies linking policies to practice to reduce health disparities between Aboriginal and non-Aboriginal Australians are also needed. Implications: Confronting the effects of racism in health services towards Aboriginal Australians is a priority requiring a multi-tiered commitment to strategies linking policy to practice to reduce health disparities between Aboriginal and non-Aboriginal Australians. Part of this strategy includes preparing undergraduates and health professionals for culturally respectful health care with education programs that are evaluated for long-term improvements to practice.